AGAINST THE POLICY THROUGH GEGURITAN (JAVANESE POEM) - Riky Zakub; Sahid Teguh Widodo; Budhi Setiawan (Universitas Sebelas Maret, 2017)
Along with the development of literature, geguritan is not just as the entertainment. It has a development change in the function and role. Means, to concern more on the form of aspiration than just as an aesthetics, ethics, meaning, and expression. These aspiration, thus, is able to lead to a resistance form. Nowadays, geguritan has an active role in emerging public’s power criticism on their awareness of current social, politic, and economic situations. This study was to analyze and investigate the resistance form of Turiyo Ragilputra through his geguritan literature work about the phenomena of populace’s affliction as the effect of government’s policy. Bledheg Segara Kidul anthology by Turiyo Ragilputra was used as the object of this study. The discourse analysis approach of Fairclough was applied, it consists three steps: description, interpretation, and explanation. The result showed that many geguritan on Turio Ragilputra’s anthology named Bledheg Segara Kidul have the obvious reaction contents about his resistance on many government’s policies which have bad effects to the populace.